Neural Network Based MPPT Controller for Solar PV Connected Induction Motor - T. Shanthi (IAES International Journal of Robotics and Automation (IJRA), 2018)
In this paper, Maximum Power Point Tracking Controller is designed based on Neural Network Controller (NNC). This controller will sense the speed of a single phase induction motor which is fed from solar panel. Maximum power point tracking (MPPT) algorithm are required in all photovoltaic (PV) system and in order to increase the efficiency of the system, Incremental Conductance algorithm which is an effective algorithm is used to extract maximum power from the solar panel which supplies an Induction motor of 1HP. To step up the voltage available from the solar panel, the SEPIC dc – dc converter is used. The main advantage of the converter is having non-inverted output. The converter acts as an interface between PV array and motor load. The entire system is modeled and simulated using MATLAB/Simulink  software.